How neonatal diet affects the long-term development of rumination behavior, rumen fermentation and feed digestion in dairy calves fed a high milk level? - Jianxin Xiao; Tianyu Chen; Rong Peng; Gibson M. Alugongo; Hui Yang; Shuai Liu; Yulin Ma; Jingjun Wang; Shengli Li; Zhijun Cao (Animal Nutrition, 2024)
This study was to investigate growth performance, rumination development, rumen fermentation and feed digestion in young calves provided high volumes (about 20% of calf birth weight) of milk with or without forage inclusion and how these parameters correlate with each other. Immediately after birth, 160 newborn Holstein female calves (41.6 ± 4.2 kg of initial BW) were randomly divided into 2 treatments: 1) starter (CON, only starter) and 2) starter and hay (HAY, both starter and hay). The calves were fed their respective experimental diets from d 4 to 84, after which they were all introduced to similar diets until the end of the experiment on d 196. Treatment had no effect on growth and structural measurements throughout the experimental period. However, treatment had an effect on the other parameters, mainly during the post-weaning period. Forage supplementation tended to reduce starter dry matter intake (P = 0.05), while increasing the forage intake (P < 0.01) and the feed-to-gain ratio (P < 0.01). HAY calves had increased neutral detergent fiber (NDF) and physically effective NDF (peNDF) intakes (P < 0.05) and tended to lower (P < 0.01) starch intake compared to CON calves. The HAY calves had a higher rumination time (P < 0.01), ruminal pH (P < 0.01), and acetate-to-propionate ratio (P = 0.05) compared to the CON calves. Spearman correlation analysis showed that rumination time was positively related to the ruminal pH at d 84 (P = 0.01) and 196 (P = 0.02). The HAY calves had similar apparent total-tract digestibility of dry matter (DM), NDF and ether extract (EE), but lower digestibility of organic matter (OM, P = 0.03), crude protein (CP, P < 0.01) and starch (P < 0.01) compared to those of the CON calves at week 12. Furthermore, there were no positive relationships between rumination time and nutrient digestibility or between rumination time per kilogram DM and nutrient digestibility. In conclusion, feeding hay to calves fed a high milk level improved rumination during the post-weaning period only, without a concomitant effect on growth performance throughout the experimental period, suggesting no detrimental effect of feeding forage in calves fed high milk level.